Neurologist-Led Management of Implantable Loop-Recorders After Embolic Stroke of Undetermined Source - Pikija, Slaven; Rösler, Cornelia; Leitner, Ursula; Zellner, Thomas; Bubel, Nele; Ganser, Bernhard; Hecker, Constantin; Mutzenbach, Johannes Sebastian (Frontiers in Neurology, 2022)
Introduction Upon completed stroke workup, etiology can not be identified in approximately one-third of patients, with an embolic stroke of undetermined source (ESUS) accounting for around 50% of these cryptogenic etiologies. Whether management of complex long-term monitoring in order to detect suspected atrial fibrillation (AFib) could be initiated and managed through a neurologist is not sufficiently investigated. Patients and methods We recruited all consecutive patients with ESUS that received implantation after neurological adjudication of Reveal LINQ® loop recorder between January 2016 and July 2020. We collected demographic, clinical, heart- and neuroimaging, laboratory, and electrocardiographic data assessed on prolonged baseline ECG monitoring - number of supraventricular (SVEs) and ventricular (VEs) extrasystolic complexes), and from pre-implantation ECG - PQ interval. AFib detection was manually supervised and determined positive when duration was over 120 seconds. Results We followed a total of 131 patients for a median of 504 days. There were 45 (34%) manually verified AFib diagnoses. In univariate analysis, earlier implantation after ESUS was associated with AFib detection (13 vs. 31 days, p=0.011). In multivariate analysis, increased rate of AFib was associated with the more prolonged PQ Interval (per 50-millisecond increase) (HR 1.99, 95% CI 1.39-2.85) and number of SVEs (HR 1.29, 95% CI 1.05-1.57) measured on pre-implantation ECG. Conclusion We observed similar predictors for Afib after ESUS, albeit with higher frequency than previously reported. The neurologist-led decision, management, and evaluation of ILR after ESUS is feasible.